Sustainability as an integrative principle: The role of international law in Arctic resource development. (22nd December 2020) - Shibata, Akiho; Chuffart, Romain
Abstract: This article addresses the normative potential of the principle of sustainability to integrate the rules, principles, and procedures of international law applicable in the Arctic, so that Arctic international law can be posited more holistically and systematically. The holistic and integrative approach towards international law is particularly called for in the context of the Arctic, as the inextricable interconnectedness between its changing natural environments, its societal particularities, and its economic and industrial potential is the fundamental characteristic of the Arctic. In line with the purpose of the special issue, this article takes up a harder case of sustainability, in addressing Arctic mineral resource development. This article posits the principle of sustainability as a principle with an integrative function operating behind the primary norms relating to resource development at the international law level. In response to the claim of fragmented nature of the law at issue, this article calls for an academic examination into the normative function of the sustainability principle to forge the relevant and evolving norms applicable in the specific context of the Arctic mineral resource development towards an integral, coherent whole. This aim will be pursued using the analytical methodology employed by the International Law Commission's (ILC) work on the "fragmentation of international law" (2006) and the "principle of integration" as identified by the International Law Association's (ILA) work on the international law relating to sustainable development (2002–12). Finally, as an initial attempt to articulate the legal reasoning for such integration, this article examines the legal institution of environmental impact assessment (EIA) as a tool to present a holistic view of the international law on Arctic mineral resource development.